Characteristics of the Waviness End-Face Mechanical Seal in Reactor Coolant Pump Considering the Viscosity-Temperature Effect - Ma, Yu; Wang, Ya-Hui; Zhou, Hai-Chun; Su, Wen-Tao (Frontiers in Energy Research, 2021)
Mechanical seals prevents flow leakages in reactor coolant pumps thus playing an important role in their operational safety. However, their operational performance depends on different parameters, the seal geometrical design and the sealing medium characteristics among others. This study investigates the main performances of the waviness end-face mechanical seal, considering the effect of fluid flow and thermal characteristics. The involved coupled thermal-hydraulic process is simulated using the OpenFOAM, based on the coupled Navier-Stokes and energy balance equations. Study results showed that the viscosity-temperature effect may increase the flow leakage, and decrease both the opening force and the liquid film stiffness. The later may be decreased to negative values under specific conditions. It’s therefore generally found that visco-thermal characteristics of the sealing medium may negatively affect mechanical seal’s operational stability. On the other hand, from the perspective of liquid film temperature rise, the visco-thermal effect may lead to the regulation of the temperature rise in the liquid film, which improves the mechanical seal’s operational safety in some aspects. Through a comprehensive analysis, the optimal structural parameters of the waviness mechanical seal investigated in this study are found to be hi = 2.5μm, β = 900μrad (Rd-Ri)/(Ro-Ri) = 0.2, α = 0.8, and k = 9.